Medication Adherence Rate in Arab Patients With Cardiovascular Disease: A Systematic Review. (September 2022) - Alomari, Albara; Alananzeh, Ibrahim; Lord, Heidi; Abdulla Al-Lenjawi, Badriya; Fernandez, Ritin
Background: Cardiovascular disease (CVD) is one of the most common chronic illnesses in the Eastern Mediterranean. There have been few studies on medication adherence in Arab patients with CVD. Aim: To investigate the rates and the reasons for medication adherence in Arab patients with CVD. Methodology: The Joanna Briggs Institute methodology for prevalence systematic reviews was used. MEDLINE, EMCARE, CINAHL, Scopus, Science Direct, PsychINFO, and the Cochrane Central Register of Controlled Trials were searched. Results: Thirteen quantitative studies on medication adherence in Arab adult CVD patients were included. Pooled data from nine studies demonstrated that 53.2% (95% confidence interval = [51.2%, 55.1%]) of patients were adherent to their medications. Reasons for nonadherence to medication include personal factors, understanding, and complexity of treatment regimes, medication knowledge and structural barriers. Conclusion: Medication adherence appears to have a social gradient, and families should be actively involved in future strategies to increase medication adherence.